Movimentos identitários docentes: ecos de um projeto pedagógico na constituição profissional de professores de uma escola da rede municipal de ensino - Cipriano, Eliana Cristina Zanette (2013)
This research aimed to identify the present features in the movement of identity formation of elementary school teachers, starting from the perspective of their comprehension in respect of the attributions and belongings emerging from the situations lived in their training process and from possible crisis which happened in circumstances of change. For this aim, we questioned in what measure an important project for a school, in a specific time of the educational management, remained in the practices of the teachers reflecting themselves in behaviors that show accession and reframing of these practices in the constitution of their identities, even after changes occurred in the educational system and in the school management. There has been used as theoretical reference the studies regarding the identity constitution in Dubar (1998, 2005, 2009 and 2011). The realm of continued teacher training is fundamented in Placco (2001, 2002, 2008 and 2010), Imbernón (2010), Tardif (2000 and 2011), Almeida (2002 and 2003) and others. The research instruments were semi-structured interviews performed with 3 teachers from the first cycles of an elementary municipal school in the interior of Sao Paulo state. These teachers took part in educational structure changes of this unity from 2005 to 2012. The analysis of the data enabled to find out how a continued training project can remain in the practices of the teachers. They can give them important elements that echo in their identity constitution even after changes in the school management and in the implementation of didactic material. It is defended that a purposed training project which is taken seriously by the teachers and the training management team generates outstanding identitary processes